2019
DOI: 10.1186/s12888-019-2220-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between adherence to a Dietary Approach to Stop Hypertension (DASH) dietary pattern and insomnia

Abstract: Background Adherence to a DASH- style diet has been reported to be associated with several health-related outcomes. A limited number of reports suggest that diet is an important behavioral determinant of insomnia. The current study aimed to explore the relationship between adherence to a DASH diet and the prevalence of insomnia in adolescent girls. Methods A total of 488 adolescent girls aged 12–18 years old were recruited from different regions of Khorasan Razavi in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
1
22
1
Order By: Relevance
“…Eating habits modification is a potential approach to prevent sleep complications. Rostami and co-researchers demonstrated that greater commitment to a DASH diet is associated with lower prevalence of insomnia [40]. Results of the present study indicated that sweetened beverage intake was associated with grater odds of insomnia.…”
Section: Discussionsupporting
confidence: 49%
“…Eating habits modification is a potential approach to prevent sleep complications. Rostami and co-researchers demonstrated that greater commitment to a DASH diet is associated with lower prevalence of insomnia [40]. Results of the present study indicated that sweetened beverage intake was associated with grater odds of insomnia.…”
Section: Discussionsupporting
confidence: 49%
“…Pahlavani et al investigated the correlation between adherence to the DASH dietary pattern and daytime sleepiness score in 535 adolescent girls in Iran; the results of the their study shed light on the inverse association between adherence to DASH diet and daytime sleepiness score [ 13 ]. Another similar study on 488 adolescent girls in Iran revealed that high adherence to the DASH-style diet was associated with a lower odds of insomnia in comparison to subjects with the lowest adherence [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional study was performed among Iranian male adults working in different healthcare centers affiliated to Baqiyatallah University of Medical Science across Tehran province from September 2020 to March 2021. Using a previous study performed by Rostami et al [ 15 ] investigating the association of adherence to the DASH style diet and insomnia, the minimum required sample size was calculated as 323, with alpha value and power set at 0.05 (2-sided) and 80%, respectively. However, to increase the power of our study we recruited 400 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…33 We have previously shown that following DASH diet reduces insomnia in adolescents. 34 However, in another study conducted among young women, it has been shown that short sleep duration was significantly associated with low quality of diet. 35 Another study found that following a diet with low inflammatory index (such as DASH diet) improved sleep quality.…”
Section: Discussionmentioning
confidence: 98%